PENGARUH PENERAPAN MANAJEMEN PENDIDIKAN BERBASIS MASYARAKAT TERHADAP PRESTASI PESERTA DIDIK - Sudarmi Ismail (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2008)
Applying of education Management being based on such society in this article is where education system walk as according to what wanted by society or competitor educated, thereby will be reached by a same target between goverment and society or competitor educated by about target carrying out of a education system